Understanding the Site‐Selective Electrocatalytic Co‐Reduction Mechanism for Green Urea Synthesis Using Copper Phthalocyanine Nanotubes. (16th May 2022) - Mukherjee, Jit; Paul, Sourav; Adalder, Ashadul; Kapse, Samadhan; Thapa, Ranjit; Mandal, Sumit; Ghorai, Biswajit; Sarkar, Sougata; Ghorai, Uttam Kumar
Abstract: Green synthesis of urea under ambient conditions by electrochemical co‐reduction of N2 and CO2 gases using effective electrocatalyst essentially pushes the conventional two steps (N2  + H2  = NH3 and NH3  + CO2  = CO(NH2 )2 ) industrial process at high temperature and high pressure, to the brink. The single step electrochemical green urea synthesis process has hit a roadblock due to the lack of efficient and economically viable electrocatalyst with multiple active sites for dual reduction of N2 and CO2 gas molecules to urea. Herein, copper phthalocyanine nanotubes (CuPc NTs) having multiple active sites (such as metal center, Pyrrolic‐N3, Pyrrolic‐N2, and Pyridinic‐N1) as an efficient electrocatalyst which exhibits urea yield of 143.47 µg h –1  mg –1 cat and faradaic efficiency of 12.99% at –0.6 V versus reversible hydrogen electrode by co‐reduction of N2 and CO2 are reported. Theoretical calculation suggests that Pyridinic‐N1 and Cu centers are responsible to form CN bonds for urea by co‐reduction of N2 to NN* and CO2 to *CO, respectively. This study provides the new mechanistic insight about the successful electro‐reduction of dual gases (N2 and CO2 ) in a single molecule as well as rational design of efficient noble metal‐free electrocatalyst for the synthesis of green urea. Abstract : Unlike the extravagant industrial process, electrochemical urea synthesis is a green propitious alternate route to convert abundant nitrogen and green‐house CO2 to urea in a single step with yield rate of 143.47 µg h –1  mg –1 cat using copper phthalocyanine nanotubes at standard temperature and pressure. This study provides new mechanistic insight about successful co‐reduction of N2 and CO2 in a single entity.